THE USE OF JURISPRUDENCE IN INDONESIAN LAW COURT AS A CIVIL LAW COUNTRY - Regina Cyrilla Candra (Problematika Hukum, 2020)
Jurisprudence refers to the decisions made by earlier judges regarding cases that are not covered by the law and which serve as a model for later judges when deciding cases of a like nature. The Supreme Court is an entity with judicial authority in Indonesia and has the authority to publish rulings. As a civil law country, Indonesian law courts do not use jurisprudence as a main legal source. Court judgments under this system are predicated on pertinent laws and regulations, such as the 1945 Constitution, MPR Decrees, Laws, Government Regulations, Presidential Decrees, Supreme Court, Ministerial Decrees, and others. This means that the judge's judgement, which is based on the facts or the available evidence, has some latitude. On the contrary, some countries use common law as their legal system. This legal system favours customary law, which changes over time in accordance with societal changes. In order to ensure that the law is always consistent with a feeling of justice and advantages that are felt immediately by the community, it was established via a judicial institution with a jurisprudence system that is regarded to be superior. Although the Indonesian legal system does not operate on a precedent system, general court judges or judges in lower-level courts are nonetheless required to take the Supreme Court's rulings seriously. This paper will be written as a discussion of how Indonesian law court as a civil law country utilises the jurisprudence, which is the product of common law system, even when it is not commonly used. This paper will also be written to elaborate the comparison between the use of jurisprudence in civil law countries such as Indonesia, and the origin countries that are using the common law system.Keywords: Jurisprudence, Indonesian Law Court, Civil Law Country